KNOWLEDGE AND PRESCRIBING PRACTICE OF AMUBULATORY CARE PHYSICIANS ABOUT DISTINCT ANTIBIOTICSTOWARDS TRIVIALRESPIRATORY TRACT INFECTED PATIENTS: STRATEGIES FOR OPTIMAL OUTCOMES AND MINIMIZED RESISTANCE - Kareemulla, Shaik; SaiPravalika, S. K.; Venkateswarlu, Govindu; Khan, P. Nishad; Sreeharinadh, K. (Asian Journal of Pharmaceutical Research and Development, 2018)
According to World Health Organization (WHO), respiratory tract infections kill 2.6 million children every year worldwide so, it is recognized as the leading cause of morbidity and mortality. Respiratory tract diseases are quite prevalent & more dangerous to the people with weak immune system function. The study was carried out for a period of 90 to 100 days in Rajiv Gandhi Institute of Medical Sciences (RIMS), Kadapa. Antibiotics are prescribed based on symptoms and laboratory investigations. It is a single centered, prospective observational study. Subjects of both genders who indicated with any one antibiotic or its combination are taken in our study and patients who had co morbid pathological conditions also included. Pediatrics, pregnant women and surgical cases were excluded from the study.60 patients (Ambulatory patients) were collected. 36 were male and 24 were female. 20 patients were found to be Literates and 40 patients were Illiterates. 38 patients belong to Lower class, 17 patients belong to Middle class and 5 patients belong to Upper class. 9 patients belong to 15-30 years of age group, 21 patients belong to 31-45 years of age group, 16 patients belong to 46-60 years of age. Ceftriaxone is prescribed in 24 patients, Azithromycin is prescribed in 17 patients, Levofloxacin is prescribed in 7 patients, Ceftriaxone + Augmentin is prescribed in 12 patients.Drug utilization studies used to analyze the different aspects of the use of drugs and to implement ways of improving therapeutic quality. In the present study, pneumonia diagnosed patients (12 patients) received antibiotic combination regimen, while other common respiratory disease patients (48 patients) received single antibiotic during treatment. All the prescribed antibiotics belong to broad spectrums that are effective against most of causative organisms such as Streptococcus, Staphylococcus, Mycoplasma, Klebsiella, Hemophilus etc. In our study, it was also found that, physicians prescribed correct drug in correct dose at correct time through right route of administration for right duration of treatment, it clearly implies that most of the prescriptions found to be Rational.